2017
DOI: 10.1111/desc.12587
|View full text |Cite
|
Sign up to set email alerts
|

Memory in 3‐month‐old infants benefits from a short nap

Abstract: A broad range of studies demonstrate that sleep has a facilitating role in memory consolidation (see Rasch & Born, ). Whether sleep-dependent memory consolidation is also apparent in infants in their first few months of life has not been investigated. We demonstrate that 3-month-old infants only remember a cartoon face approximately 1.5-2 hours after its first presentation when a period of sleep followed learning. Furthermore, habituation time, that is, the time to become bored with a stimulus shown repetitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 45 publications
2
21
0
Order By: Relevance
“…Indeed, experimental studies have provided evidence that sleep supports the retention and reorganization of memories even in infancy (Friedrich, Wilhelm, Born, & Friederici, ; Friedrich, Wilhelm, Mölle, Born, & Friederici, ; Gómez, Bootzin, & Nadel, ; Horváth, Hannon, Ujma, Gombos, & Plunkett, ; Horváth, Liu, & Plunkett, ; Horváth, Myers, Foster, & Plunkett, ; Hupbach, Gomez, Bootzin, & Nadel, ; Konrad, Herbert, Schneider, Lorek, & Seehagen, ; Konrad, Herbert, Schneider, & Seehagen, ; Seehagen, Konrad, Herbert, & Schneider, ; Simon et al., ). For the consolidation of early lexical–semantic memories, a benefit of sleep has been demonstrated by analyzing the looking behavior in 16‐month‐olds (Horváth et al., , ) and by measuring event‐related potentials (ERPs) in groups of 6‐ to 8‐ and 9‐ to 16‐month‐olds (Friedrich et al., , ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, experimental studies have provided evidence that sleep supports the retention and reorganization of memories even in infancy (Friedrich, Wilhelm, Born, & Friederici, ; Friedrich, Wilhelm, Mölle, Born, & Friederici, ; Gómez, Bootzin, & Nadel, ; Horváth, Hannon, Ujma, Gombos, & Plunkett, ; Horváth, Liu, & Plunkett, ; Horváth, Myers, Foster, & Plunkett, ; Hupbach, Gomez, Bootzin, & Nadel, ; Konrad, Herbert, Schneider, Lorek, & Seehagen, ; Konrad, Herbert, Schneider, & Seehagen, ; Seehagen, Konrad, Herbert, & Schneider, ; Simon et al., ). For the consolidation of early lexical–semantic memories, a benefit of sleep has been demonstrated by analyzing the looking behavior in 16‐month‐olds (Horváth et al., , ) and by measuring event‐related potentials (ERPs) in groups of 6‐ to 8‐ and 9‐ to 16‐month‐olds (Friedrich et al., , ).…”
Section: Introductionmentioning
confidence: 99%
“…Sleep spindles are relatively stable in an individual and their trait‐like characteristics are related to an individual's perceptual, cognitive, and learning abilities (Bódizs et al., ; Fogel, Nader, Cote, & Smith, ; Schabus et al., , ). Individual abilities as reflected in spindle characteristics may affect stimulus processing already in infancy, as it appeared to be the case for visual habituation in 3‐month‐olds (Horváth et al., ). In the study with 6‐ to 8‐month‐old infants, however, not only spindle activity itself, but also its individually normalized local increase over the relevant central–parietal regions with reference to remaining regions was related to the generalization of the category–word pairings (Friedrich et al., ), which suggests that trait‐like differences in spindle activity do not fully explain the spindle‐related improvement in memory in these studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, 6‐ and 12‐month‐olds who napped after observing modeled target actions exhibited higher levels of deferred imitation as compared to infants who did not nap (Seehagen, Konrad, Herbert, & Schneider, ). Recent work with 3‐month‐olds has also revealed that napping was critical to subsequent visual recognition memory (Horvath, Hannon, Ujma, Gombos, & Plunkett, ). Empirical investigations of sleep offer a novel tool to examine memory consolidation processes during infancy, including contributions to individual differences in memory.…”
Section: Potential Mechanisms and Sources Of Variation In Memory Devementioning
confidence: 99%
“…It is well established that sleep after encoding facilitates the consolidation of both declarative and nondeclarative memories in human adults (Rasch & Born, ). A small but growing body of experimental research has revealed that postlearning sleep also facilitates the consolidation of recently encoded memories in infants across different paradigms (Friedrich, Wilhelm, Born, & Friederici, ; Horváth, Hannon, Ujma, Gombos, & Plunkett, ; Horváth, Myers, Foster, & Plunkett, ; Konrad, Herbert, Schneider, & Seehagen, ; Seehagen, Konrad, Herbert, & Schneider, ). For example, in a visual recognition memory paradigm, 3‐month‐olds were repeatedly shown a cartoon‐style face on a screen until their attention declined below a predefined criterion.…”
Section: Memory and Sleepmentioning
confidence: 99%